Reflective ESP Practice: Teachers' Beliefs, Methods, and Negotiating Institutional Realities - Salsabila Ramadhani Imanda; Niamika El Khoiri; Sari Karmina (South Sulawesi Education Development (SSED), 2025)
This single-case study explores the belief-practice dynamics of Pippa, an experienced English for Specific Purposes (ESP) teacher in an Economics Development program, utilizing a reflective practice approach. The study investigated the extent to which her pedagogical beliefs align with her classroom practices, and how institutional realities mediate this relationship. Data were triangulated through a pre-observation interview, classroom observation of an academic writing session (biography writing), and a critical post-observation interview. Thematic analysis of the data revealed a complex interplay characterized by conditional alignment and institutional mediation. While Pippa professed a belief in consistently correcting errors and promoting the use of English, her practice demonstrated strategic adaptation: L1 (Indonesian) use was tolerated to maintain student confidence, and pronunciation correction was applied selectively based on task demands (e.g., minimal correction during reading aloud versus stricter application during speaking tasks). Crucially, divergence was found to be largely driven by external constraints that emerged from the data, including the student level mismatch (low-beginner students in an ESP course) and the institutional culture emphasizing